Equiaxial Strain Modulates Adipose-derived Stem Cell Differentiation within 3D Biphasic Scaffolds towards Annulus Fibrosus. Issue 1 (December 2017) - Elsaadany, Mostafa; Winters, Kayla; Adams, Sarah; Stasuk, Alexander; Ayan, Halim; Yildirim-Ayan, Eda
Abstract Recurrence of intervertebral disc (IVD) herniation is the most important factor leading to chronic low back pain and subsequent disability after discectomy. Efficacious annulus fibrosus (AF) repair strategy that delivers cells and biologics to IVD injury site is needed to limit the progression of disc degeneration and promote disc self-regeneration capacities after discectomy procedures. In this study, a biphasic mechanically-conditioned scaffold encapsulated with human adipose-derived stem cells (ASCs) is studied as a potential treatment strategy for AF defects. Equiaxial strains and frequencies were applied to ASCs-encapsulated scaffolds to identify the optimal loading modality to induce AF differentiation. Equiaxial loading resulted in 2–4 folds increase in secretion of extracellular matrix proteins and the reorganization of the matrix fibers and elongations of the cells along the load direction. Further, the equiaxial load induced region-specific differentiation of ASCs within the inner and outer regions of the biphasic scaffolds. Gene expression of AF markers was upregulated with 5–30 folds within the equiaxially loaded biphasic scaffolds compared to unstrained samples. The results suggest that there is a specific value of equiaxial strain favorable to differentiate ASCs towards AF lineage and that ASCs-embedded biphasic scaffold can potentially be utilized to repair the AF defects.